Real-world evaluation of quality of life, effectiveness, and safety of aflibercept plus FOLFIRI in patients with metastatic colorectal cancer: the prospective QoLiTrap study - Hofheinz, Ralf-Dieter; Anchisi, Sandro; Grünberger, Birgit; Derigs, Hans G.; Zahn, Mark-Oliver; Geffriaud-Ricouard, Christine; Gueldner, Max; Windemuth-Kieselbach, Christine; Pederiva, Stefanie; Bohanes, Pierre; Scholten, Felicitas; Piringer, Gudrun; et al. (Cancers, 2022)
Aflibercept plus FOLFIRI prolongs overall survival (OS) in patients with metastatic colorectal cancer after the failure of oxaliplatin-containing therapy. QoLiTrap prospectively evaluated the quality of life (QoL) and effectiveness of this regimen in daily clinical practice, according to RAS status, sex, and prior targeted therapy, especially epidermal growth factor receptor inhibitors (EGFR-I). The primary endpoint was the percentage of patients whose EORTC QLQ-C30 global health status (GHS) improved or reduced by <5% from baseline during the first 12 weeks of therapy. Secondary endpoints included objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and safety. One thousand two hundred and seventy-seven patients were treated with aflibercept plus FOLFIRI and 872 were evaluable for QoL. GHS improved or decreased by <5% in 40.3% of cases. The ORR was 20.8%, the median PFS was 7.8 months (95% confidence interval (CI), 7.3-8.3), and the median OS was 14.4 months (95% CI, 13.1-18.1). After prior EGFR-I, the ORR was 23.7%, median PFS was 9.4 months (95% CI, 6.5-12.9), and median OS was 17.4 months (95% CI, 10.5-33.7). The safety profile was consistent with previously reported data. Aflibercept plus FOLFIRI given in daily practice maintained QoL in mCRC patients, was associated with a high objective tumor response, and retained its activity regardless of sex, RAS status, and prior EGFR-I therapy.
Gesehen am 28.11.2023